2017
DOI: 10.1002/ange.201703191
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant Phase Transition Drives Dynamic Substructure Formation in Ribonucleoprotein Droplets

Abstract: Intracellular ribonucleoprotein (RNP) granules are membrane‐less droplet organelles that are thought to regulate posttranscriptional gene expression. While liquid–liquid phase separation may drive RNP granule assembly, the mechanisms underlying their supramolecular dynamics and internal organization remain poorly understood. Herein, we demonstrate that RNA, a primary component of RNP granules, can modulate the phase behavior of RNPs by controlling both droplet assembly and dissolution in vitro. Monotonically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
218
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(236 citation statements)
references
References 32 publications
18
218
0
Order By: Relevance
“…where n 2 is small. This limited range of attraction allows for re-entrant behavior similar to that seen for RNA condensation due to charge-charge interactions [29].…”
Section: A Spop-spop Interactions Cause the Formation Of Linear Rodsmentioning
confidence: 83%
“…where n 2 is small. This limited range of attraction allows for re-entrant behavior similar to that seen for RNA condensation due to charge-charge interactions [29].…”
Section: A Spop-spop Interactions Cause the Formation Of Linear Rodsmentioning
confidence: 83%
“…This charge inversion suggests that the stoichiometry of these fuzzy protein-RNA assemblies is not fixed but varies with the mixture composition. Interestingly, we observed that sudden jumps in RNA-to-LCD stoichiometry can lead to the formation of transient hollow droplet topologies under nonequilibrium conditions (18). Although, these vacuolated structures were observed only as fleeting intermediates during reentrant dissolution of protein-RNA condensates, their occurrence nevertheless suggested that associative RNA-protein systems may have access to complex morphologies distinct from isotropic liquid droplets.…”
Section: Introductionmentioning
confidence: 82%
“…Recently, we demonstrated that RNA can mediate a reentrant phase transition of cationic ribonucleoproteins containing arginine-rich low complexity domains (LCDs) through long-range electrostatic interactions (18,19). At sub-stoichiometric regime, RNA triggers ribonucleoprotein (RNP) phase separation whereas at super-stoichiometric ratio, excess RNA leads to droplet dissolution due to charge inversion on the surface of RNP-RNA complexes (18). This charge inversion suggests that the stoichiometry of these fuzzy protein-RNA assemblies is not fixed but varies with the mixture composition.…”
Section: Introductionmentioning
confidence: 99%
“…While their promotional effects have been noted in a number of studies 10,13,23,25,27,30,31,44,45,50 , their turnover into suppressors at high concentrations has also been recognized in other studies 21,34,46,49,52 . The suppressive effects of high-concentrations RNAs may explain their ability to keep ribonucleoproteins soluble 34,35 .…”
Section: Introductionmentioning
confidence: 99%